A Case Report: Hepatic artery pseudoaneurysm causing life-threatening haemobilia. (September 2021) - Shelton, J.; Raviraj, S.
Abstract: Introduction & importance: Hepatic artery aneurysms (HAA) are rare and it accounts 20% of all visceral artery aneurysms. Commonly HAAs are autopsy findings, but rupture and bleeding carrying significant morbidity and can manifest as haemobilia. Case presentation: A 63-year-old Sri Lankan male presented with severe melaena upper abdominal pain and features of obstructive jaundice was found to have a giant pseudoaneurysm at the right hepatic artery with the possible arterio-biliary fistula. The etiology for the pseudoaneurysm was not identified. Despite massive transfusion, the patient died before the endovascular intervention. Clinical discussion: Atherosclerosis is the leading cause of HAA formation but can be associated with connective tissue disorders and arteritis. Most of the HAA are asymptomatic. Aneurysms can be managed with surgical or endovascular interventions. Conclusion: Life-threatening haemobilia is a notorious complication of the rapture of HAA into the biliary system. The incidents of hepatic artery aneurysms and pseudoaneurysms due to percutaneous transhepatic interventions and minimal invasive hepatobiliary surgeries are in the rising trend. Nonleaking VAA can be best treated with endovascular treatment. The knowledge on this topic is important for the early detection and intervention of this rare entity. Highlights: Massive Gastrointestinal bleeding can be haemobilia. Rupture of vascular aneurysms into the biliary system can cause severe haemobilia. Incidents of Hepatic artery aneurysms due to minimal invasive transhepatic procedures are in a rising trend. Non-leaking Visceral artery aneurysms can be managed best with Endovascular treatment.